The diagnostic value of circulating microRNAs as biomarkers for coronary artery disease: A meta‑analysis - Qin Fang; Yuanjiang Liao; Zhonglin Xu; Jinmei Li; Xiaoliang Zhang; Yunhong Wang (Anatolian Journal of Cardiology, 2020)
Objective: In recent years, research on microRNAs (miRNAs) associated with coronary artery disease (CAD) has attracted considerable attention. However, findings of these studies on the validity of circulating miRNAs in CAD diagnosis are controversial. A meta-analysis was therefore conducted to determine the potential value of miRNAs as biomarkers in CAD diagnosis. Methods: Relevant documents on miRNAs expression levels in the diagnosis of CAD were searched and collected from Pubmed, Embase, and Web of Science. They were collected from the time of inception of the database till January 31, 2020. A meta-analysis was conducted using Stata14.0 software. Forest maps were studied and a comprehensive evaluation of the diagnostic value of the expression levels of mRNAs in CAD was conducted using statistical indicators such as the summary receiver operating characteristic curve. Results: Overall, 14 studies were included, with 38 data sets, involving 29 miRNAs with 846 cases and 898 controls. The meta-analysis revealed that the average sensitivity and specificity of miRNAs for CAD diagnosis were 0.80 (0.75–0.84) and 0.78 (0.75–0.81), respectively. The positive likelihood, negative likelihood, and diagnostic odds ratios were 3.7 (3.1–4.4), 0.26 (0.21–0.33), and 14 (10–21), respectively, and the area under the curve was 0.85 (0.82–0.88). Subgroup analysis revealed that the accuracy in the Asian population was higher than that in the non-Asian population. Multiple miRNAs may be more diagnostically accurate than single miRNAs. MiRNAs in whole blood were more accurate than those in plasma, serum, and peripheral blood mononuclear cells. The diagnostic performance of the quantitative real-time polymerase chain reaction group was better than that of the qPCR group. Conclusion: According to our study, miRNAs may be a new, non-invasive diagnostic tool for the diagnosis of CAD. As a screening tool in clinical practice, it has potential diagnostic value and is worthy of clinical promotion. Considering the number and quality of the studies included in this meta-analysis, the above conclusion requires more quality research to verify it.